Perlindungan Ekspresi Budaya Tradisional Bali Terhadap Klaim PT Karya Tangan Indah (Studi Kasus Putusan No. 823/K/Pid.Sus/2009) - Verius Wiro, Octa (LPPM Universitas Ekasakti Padang, 2024)
Ketut Deni Aryasa was brought to the court as a defendant and was acquitted based on Denpasar District Court Decision Number: 341/Pid.Sus/2014/PN.Dps and corroborated in the Supreme Court Decision Number 823 K/Pid.Sus/2009. The verdict is related to the criminal offense of copyright infringement, intentionally and without the right to do the act of publishing or reproducing a work. (Article 72 paragraph (1) of Law No. 19 Year 2002 on Copyright). This case not only involves the defendant, but also involves John Hardy Limited, PT Karya Tangan Indah, and Balinese silver craftsmen. The silversmiths were involved because they considered the object of the case to be their traditional cultural expression, and it was found that many other traditional cultural expressions had been registered by foreign parties. GRTKF was a hot topic at that time, even until now it is still an issue, and this case has also become a discussion at WIPO in its discussion about GRTKF. The object of this research is traditional cultural expressions and copyright (case study in Supreme Court Decision Number 823 K/Pid.Sus/2009). This decision illustrates that traditional cultural expressions are regulated in copyright and some related rules in Indonesia. However, the regulation related to traditional cultural expressions is still not effective. It can be said that traditional cultural expressions have not been maximally protected. Concerns arise over the utilization of traditional cultural expressions by foreign parties, but to the detriment of the communal community where the traditional cultural expressions originate.